Deep Dark Futures: Foresighting Human Impacts on Mesopelagic Ecosystem Services - Ben Scoulding; Alistair J. Hobday; Rowan Trebilco; Heidi Pethybridge; Ingrid van Putten; Katherine Baker; Karen Evans; David Green; Eriko Hoshino; Haris Kunnath; Clothilde Langlais; Tim P. Lynch; et al. (Fish and Fisheries, 2026)
Most of the global mesopelagic zone lies beyond the jurisdiction of any single government or entity, making equitable access and sustainable management for ecosystem services (ES) difficult. Here, a foresighting approach was used to examine the plausible consequences of four speculative scenarios of human activity on the mesopelagic zone and its associated ES. Large‐scale Harvest represented the provisioning ES, with concerns over unsustainable removal of mesopelagic biota. Climate Mitigation, a regulating ES, involved harvesting and then dumping mesopelagic biota to maximise carbon drawdown. In Geopolitical Manoeuvring, the scenario focused on cultural ES; mesopelagic fisheries were used as a geopolitical instrument to assert claims over ocean spaces. Finally, Mineral Extraction, a supporting ES, considered the impact of deep‐sea mining on mesopelagic ecosystems. Drivers and indicators for each scenario were identified, and qualitative network models were created to assess impact on the different system components using press perturbations. Model outputs highlighted the central role that mesopelagic biota play in supporting and regulating other ecosystem components and the likely negative impacts of reduced biomass on higher order predators and ocean carbon storage. Interestingly, biological indicators performed poorly as early warning signals of change across all scenarios; instead, the most effective indicators were related to science and technology, economics and governance. International agreements for sustainable use of the mesopelagic zone are needed to avoid loss of ES underpinning all scenarios. While this foresighting focused on the mesopelagic zone, the approach of developing scenarios, models and indicators has broader applicability to studies of other systems.